Evidence of Freezing Pressure in Sea Ice Discrete Brine Inclusions and Its Impact on Aqueous‐Gaseous Equilibrium. Issue 3 (14th March 2019) - Crabeck, O.; Galley, R. J.; Mercury, L.; Delille, B.; Tison, J.‐L.; Rysgaard, S.
Abstract: Sea ice in part controls surface water properties and the ocean‐atmosphere exchange of greenhouse gases at high latitudes. In sea ice, gas exists dissolved in brine and as air bubbles contained in liquid brine inclusions or as bubbles trapped directly within the ice matrix. Current research on gas dynamics within the ocean‐sea ice‐atmosphere interface has been based on the premise that brine with dissolved air becomes supersaturated with respect to the atmosphere during ice growth. Based on Henry's law, gas bubbles within brine should grow when brine reaches saturation during cooling, given that the total partial pressure of atmospheric gases is above the implicit pressure in brine of 1 atm. Using high‐resolution light microscopy time series imagery of gas bubble evolution inside discrete brine pockets, we observed bubbles shrinking during cooling events in response to the development of freezing pressure above 3 atm. During warming of discrete brine pockets, existing bubbles expand and new bubbles nucleate in response to depressurization. Pressure variation within these inclusions has direct impacts on aqueous‐gaseous equilibrium, indicating that Henry's law at a constant pressure of 1 atm is inadequate to assess the partitioning between dissolved and gaseous fractions of gas in sea ice. This new evidence of pressure build‐up in discrete brine inclusions controlling the solubility of gas and nucleation of bubbles in these inclusions has the potential to affect the transport pathways of air bubbles and dissolved gases within sea ice‐ocean‐atmosphere interface and modifies brine biochemical properties. Plain Language Summary: Sea ice plays an important role in controlling surface water properties and the ocean‐atmosphere exchange of greenhouse gases at high latitudes. Within sea ice, gas exists dissolved in brine and as air bubbles contained in liquid brine inclusions. The amount of gas dissolved in brine as well as the amount of gas contained in air bubbles depends of the aqueous‐gaseous equilibrium described by the Henry's law. Until now, it is assumed that the pressure in sea ice brine inclusions is 1 atm (standard pressure condition). Our work reveals visual evidence of variation of pressure within discrete brine pockets. These pressure regimes modify the aqueous‐gaseous equilibrium and induce bubbles to shrink during cooling and enlarge or nucleate during warming. This new evidence of pressure build‐up in discrete brine controlling the solubility of gas has the potential to affect the transport pathways of air bubbles and dissolved gases between ocean and atmosphere in the presence of sea ice and to modify brine biochemical properties. Key Points: In discrete brine pockets, our observations show decreased bubble volumes during cooling and increased bubble volumes during warming Freezing pressure builds up in cooled brine inclusions when they evolve as closed systems. This process results in bubble compression These considerations suggest that the use of Henry's law at constant atmospheric pressure is inadequate to describe the aqueous‐gaseous equilibrium in discrete brine inclusions in sea ice